Systematic review of Buzhong Yiqi method in alleviating cancer-related fatigue: a meta-analysis and exploratory network pharmacology approach - Zeng, Ji; Wu, Qi; Meng, Xu-Dong; Wang, Jian (Frontiers in Pharmacology, 2024)
Objectives. CRF is a prevalent and distressing symptom experienced by many cancer patients, necessitating effective treatments. This study utilizes meta-analysis and network pharmacology to comprehensively assess the efficacy of the BZYQ prescription in alleviating cancer-related fatigue and to preliminarily explore the mechanism of its core drugs. Methods. We included RCTs in cancer patients. The inclusion criteria encompassed a diagnosis of CRF, without limitation on cancer type, the experimental group receiving Buzhong Yiqi prescription, the control group receiving conventional treatment, patients awaiting treatment, and articles published in either English or Chinese. We conducted a search through February 29, 2024, across PubMed, Cochrane Database of Systematic Reviews, CENTRAL, CBM, CNKI, WANFANG Database, and Weipu Database. Journal articles that met the inclusion criteria were selected for inclusion. Two independent investigators evaluated the quality of the included studies. A meta-analysis was performed utilizing the Stata 12.0 software package, where estimates of cancer-related fatigue were aggregated through the application of a random-effects model. We employed the Cochrane Risk of Bias Tool to evaluate potential biases in RCTs. The primary outcome measures utilized to assess the efficacy and safety of CRF treatment comprised PFS-R and the EORTC QLQ-C30. The secondary outcomes encompassed the KPS score, effective rate, TCM syndrome score, and an evaluation of adverse reactions. The TCMSP was utilized to identify the active ingredients and targets of BZD. Additionally, the Drug bank, TTD, DiaGeNET, and GeneCards databases were utilized to retrieve relevant targets for CRC. The Venn diagram was employed to identify overlapping targets. Cytoscape software was utilized to construct a network of “herb-ingredient-target” and identify core targets. GO and KEGG pathway enrichment analyses were performed using R language software. Results. In comparison to the control group, patients with CRF who received BZYQ prescription exhibited marked improvements in KPS score, QLQ-C30 quality of life score, and effective rate. Conversely, PFS, TCM syndrome score, and adverse reaction assessments significantly decreased. The primary active ingredients in its core drugs may exert a positive therapeutic effect on CRF by targeting molecules such as AKT1, IL6, IL1B, , as well as through signaling pathways including TNF, IL17, TLR, NF-κB.